Problems of Food Waste Treatment аnd Ways of Their Resolving - A. P. Epishov; S. E. Zhura; A. V. Voronov (Вестник Российского экономического университета имени Г. В. Плеханова)
The problem of food waste treatment has attracted serious attention lately, as such wastes are regarded as a source of valuable biological matters. We should consider them as a resource, which can be used in the future to produce forage, fertilizers, etc. The authors carried out investigations aimed at revealing problems of food waste treatment. Analysis of the effective legal acts allows us to draw a conclusion, that the major part of these acts cannot create conditions directed to preferable and priority utilization of food wastes, therefore recommendations aimed at elimination of gaps in the field of waste regulation are advanced. First of all it is necessary to specify available definitions and introduce new ones in the field of food waste management, to ban destruction and burial of food waste, build infrastructure for separate garbage collection with obligatory use of bins for food waste. At the same time it is needed to adopt a law about food-sharing, to insert amendments into the Tax Code of the Russian Federation and to remove from the list of taxation entities food stuffs with expiring BBD in case of their free transfer. These changes could release trade enterprises from taxes and thus motivate companies not to reduce foods to the condition of food waste. Serious attention should be paid to technologies of their utilization and assessment of efficiency of technological solutions on their use in the field of food stuffs management in the Russian Federation in order to decrease amounts of food with expiring BBD and food waste.